PELATIHAN SOCIAL MEDIA MARKETING SEBAGAI STRATEGI UNTUK PENINGKATAN BRAND BINTANG DEWATA SUKSES - Ni Made Satya Utami; I Ketut Setia Sapta; Ni Luh Putu Melia Widya Pradewi (Jurnal Abdi Citra, 2026)
This activity aims to enhance the digital branding capabilities of the business partner, BDS (Bintang Dewata Sukses), through a social media marketing training focused on utilizing Instagram. Based on initial observations, BDS did not yet have an official social media account and had not implemented an effective digital marketing strategy. The provided solutions included creating an official Instagram account, basic training in social media use, an introduction to Instagram features, and content guideline development. The results showed an increase in employees’ understanding of digital marketing and the establishment of an active Instagram account as a promotional tool. This activity serves as an initial step in establishing consistent digital branding that aligns with current technological developments.